Utilization of methylene blue-adsorbed halloysite after carbonization to activate peroxymonosulfate degrading phenol: Performance and mechanism. (October 2022) - Wang, Qiang; Liu, Haibo; Zhai, Peixun; Sun, Fuwei; Chen, Tianhu; Chu, Ziyang; Chen, Dong; Zou, Xuehua
Abstract: In this study, a new low-cost carbon-based material was prepared via the carbonization of methylene blue adsorbed halloysite (CMH) at different temperatures in a nitrogen atmosphere, which was named CMH-T (T-Temperature). The performance of CMH-T was explored and the effects of initial pH values, catalyst dosage, phenol (PE) concentrations, peroxymonosulfate (PMS) concentrations, and water background compounds on PE degradation were investigated systematically. The results indicated that CMH800 exhibited the best performance to activate PMS for degrading PE. Specifically, 92% PE was degraded within 30 min with a constant rate ( k obs ) of 0.1186 min −1 in the CMH800/PMS system. Furthermore, CMH800 was efficient over a wide pH range (pH 3–9) and showed a slight inhibition to inorganic anions. Quenching experiments, electron spin resonance (ESR) analysis, and electrochemical analysis confirmed that PE was degraded through non-radical pathways dominated by single oxygen ( 1 O2 ) and mediated electron transfer processes in the CMH800/PMS system. In addition, the predicted toxicity of intermediates through ECOSAR software based on QSAR (Quantitative Structure - Activity Relationship) model indicated that most of the intermediates had a low risk to water environment. Therefore, the CMH800 has a good potential for wastewater treatment applications. Graphical abstract: Image 1 Highlights: A new carbon-based catalyst was prepared through carbonization of waste Halloysite. CMH600-900 was used for peroxymonosulfate (PMS) activation to degrade phenol. The CMH800 exhibited best performance for PMS activation. Nonradical reaction pathway was proposed as the main catalytic mechanism. The degradation pathway and the predicted toxicity of intermediates were proposed.